Pressure-accelerated dissociation of amyloid fibrils in wild-type hen lysozyme - Shah, Buddha R; Maeno, Akihiro; Matsuo, Hiroshi; Tachibana, Hideki; Akasaka, Kazuyuki (Biophysical journal, 2012)
The dynamics of amyloid fibrils, including their formation and dissociation, could be of vital importance in life. We studied the kinetics of dissociation of the amyloid fibrils from wild-type hen lysozyme at 25°C in vitro as a function of pressure using Trp fluorescence as a probe. Upon 100-fold dilution of 8 mg ml(-1) fibril solution in 80 mM NaCl, pH 2.2, no immediate change occurred in Trp fluorescence, but at pressures of 50-450 MPa the fluorescence intensity decreased rapidly with time (k(obs) = 0.00193 min(-1) at 0.1 MPa, 0.0348 min(-1) at 400 MPa). This phenomenon is attributable to the pressure-accelerated dissociation of amyloid fibrils into monomeric hen lysozyme. From the pressure dependence of the rates, which reaches a plateau at ~450 MPa, we determined the activation volume ΔV(0‡) = -32.9 ± 1.7 ml mol(monomer)(-1) and the activation compressibility Δκ(‡) = -0.0075 ± 0.0006 ml mol(monomer)(-1) bar(-1) for the dissociation reaction. The negative ΔV(0‡) and Δκ(‡) values are consistent with the notion that the amyloid fibril from wild-type hen lysozyme is in a high-volume and high-compressibility state, and the transition state for dissociation is coupled with a partial hydration of the fibril.